2013
DOI: 10.1073/pnas.1308477110
|View full text |Cite
|
Sign up to set email alerts
|

Depressed pacemaker activity of sinoatrial node myocytes contributes to the age-dependent decline in maximum heart rate

Abstract: An inexorable decline in maximum heart rate (mHR) progressively limits human aerobic capacity with advancing age. This decrease in mHR results from an age-dependent reduction in "intrinsic heart rate" (iHR), which is measured during autonomic blockade. The reduced iHR indicates, by definition, that pacemaker function of the sinoatrial node is compromised during aging. However, little is known about the properties of pacemaker myocytes in the aged sinoatrial node. Here, we show that depressed excitability of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
163
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(175 citation statements)
references
References 60 publications
11
163
1
Order By: Relevance
“…SAMs were harvested from male C57BL/6J mice of 6 -12 wk of age (Jackson Laboratories, Bar Harbor, ME) as we have previously described (16,18,38,14). Animals were anesthetized by inhalation of isoflurane and euthanized by cervical dislocation.…”
Section: Sinoatrial Myocyte Isolationmentioning
confidence: 99%
See 3 more Smart Citations
“…SAMs were harvested from male C57BL/6J mice of 6 -12 wk of age (Jackson Laboratories, Bar Harbor, ME) as we have previously described (16,18,38,14). Animals were anesthetized by inhalation of isoflurane and euthanized by cervical dislocation.…”
Section: Sinoatrial Myocyte Isolationmentioning
confidence: 99%
“…SAMs were isolated from the sinoatrial node, which was defined as the region bordered by the crista terminalis, the interatrial septum, and the superior and inferior vena cavae as in previous studies (16,18,38,14,25,33). Individual cells were initially identified visually by the presence of spontaneous contractions and by their characteristic morphology, small size, and lack of striations as we have previously described (14,16,18,38). In electrophysiological recordings, SAMs were additionally defined as cells that fired spontaneous action potentials with characteristic AP waveform parameters including a diastolic depolarization phase and a slow upstroke (14) and by the presence of If of Ͼ100 pA in response to a 1-s voltage step to Ϫ120 mV in voltage clamp experiments (see RESULTS).…”
Section: Sinoatrial Myocyte Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…An important observation is that single isolated SAN cells from mice have a slower spontaneous firing rate with aging, and clearly this cannot be explained by fibrosis. 31 In humans, detailed electrophysiological study of patients with idiopathic SND have revealed widespread conduction delay that is especially pronounced along the CT, caudal shift of the leading pacemaker and a change from a multicentric (in controls) to a unicentric site of first activation (Figure 3). 25 The molecular correlate of these changes is, at least in part, ion channel remodeling, which has been extensively investigated in aging animal models of SND.…”
Section: "Idiopathic" Sndmentioning
confidence: 99%